Analisis Kesantunan Berbahasa dalam Kumpulan Video Debat Bahasa Indonesia pada Kanal Youtube X OTKP 2 - Laila Faza Naimah; Devia Reski Novella; Ainun Rahma Dani; Dea Sheva Dwi Anggraeni; Intan Mutiara Safira; Asep Purwo Yudi Utomo; Iwan Hardi Saputro (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research examines politeness in language based on the ten maxims according to (Leech, 2014) in a collection of Indonesian language debate videos on the X OTKP 2 YouTube channel. There are several reasons why researchers conducted this research, namely that no previous researcher had chosen the title of the article and the data source. In this article has not been studied by previous researchers. The aim of this research is to determine the principles of linguistic politeness which consist of ten maxims, including the maxim of generosity, maxim of tact, approbation, modesty, obligation of S to O, obligation of O to S, agreement, opinion retincence, sympathy, and feeling reticence. This research uses a qualitative descriptive method and a pragmatic theoretical approach. The data used in this research is a collection of a number of Indonesian language debate videos. The data source comes from the X OTKP 2 YouTube channel. This research produce 177 data, 119 (67%) of obedience maxim and 58 (33%) of violations maxim. The maxim of obedience consist of Tact maxim, Approbation, Modesty, Obligation of S to O, Agreement, and Opinion Reticence. While in the violatin, there are maxim of generosity, Tact, Approbation, Modesty, Obligation of O to S, Opinion Reticence, Sympathy, and Feeling of Reticence. With this research, it is expected to provide an understanding of language politeness.